The Sandbridge SB3011 Platform. (26th April 2007) - Glossner, John; Iancu, Daniel; Moudgill, Mayan; Nacer, Gary; Jinturkar, Sanjay; Stanley, Stuart; Schulte, Michael
Abstract : This paper describes the Sandbridge Sandblaster real-time software-defined radio platform. Specifically, we describe the SB3011 system-on-a-chip multiprocessor. We describe the software development system that enables real-time execution of communications and multimedia applications. We provide results for a number of interesting communications and multimedia systems including UMTS, DVB-H, WiMAX, WiFi, and NTSC video decoding. Each processor core achieves 600 MHz at 0.9 V operation while typically dissipating 75 mW in 90 nm technology. The entire chip typically dissipates less than 500 mW at 0.9 V.